Modeling airborne pollen concentrations at an urban scale with pollen release from individual trees - Daniel S. W. Katz; Alan P. Baptist; Stuart A. Batterman (Aerobiologia, 2023)

Associations of self-reported occupational exposures and settings to ALS: a case–control study - Stephen A. Goutman; Jonathan Boss; Christopher Godwin; Bhramar Mukherjee; Eva L. Feldman; Stuart A. Batterman (International Archives of Occupational and Environmental Health, 2022)
Background Environmental exposures contribute to the pathogenesis of amyotrophic lateral sclerosis (ALS), a fatal and progressive neurological disease. Identification of these exposures is important for targeted screening and risk factor modification. Objective To identify occupational exposures that are associated with a higher risk of ALS using both survey and standard occupational classification (SOC) coding procedures, and to highlight how exposure surveys can complement SOC coding. Methods ALS participants and neurologically healthy controls recruited in Michigan completed a detailed exposure assessment on their four most recent and longest held occupations. Exposure scores were generated from the exposure survey, and occupations were assigned to SOC codes by experienced exposure scientists. Results This study included 381 ALS and 272 control participants. ALS participants reported higher duration-adjusted occupational exposure to particulate matter (OR = 1.45, 95% CI 1.19–1.78, p < 0.001), volatile organic compounds (OR = 1.22, 95% CI 1.02–1.45, p = 0.029), metals (OR = 1.48, 95% CI 1.21–1.82, p < 0.001), and combustion and diesel exhaust pollutants (OR = 1.20, 95% CI 1.01–1.43, p = 0.041) prior to ALS diagnosis, when adjusted for sex, age, and military service compared to controls. In multivariable models, only occupational exposure to metals remained significant risk (OR = 1.56, 95% CI 1.11–2.20, p = 0.011), although in an adaptive elastic net model, particulate matter (OR = 1.203), pesticides (OR = 1.015), and metals (1.334) were all selected as risk factors. Work in SOC code “Production Occupations” was associated with a higher ALS risk. SOC codes “Building and Grounds Cleaning and Maintenance Occupations”, “Construction and Extraction Occupations”, “Installation, Maintenance, and Repair Occupations”, and “Production Occupations” were all associated with a higher exposure to metals as determined using survey data. Discussion Occupational exposure to particulate matter, volatile organic compounds, metals, pesticides, and combustion and diesel exhaust and employment in “Production Occupations” was associated with an increased ALS risk in this cohort.

Urban-scale variation in pollen concentrations: a single station is insufficient to characterize daily exposure - Daniel S. W. Katz; Stuart A. Batterman (Aerobiologia, 2020)

Pollen production for 13 urban North American tree species: allometric equations for tree trunk diameter and crown area - Daniel S. W. Katz; Jonathan R. Morris; Stuart A. Batterman (Aerobiologia, 2020)

Absence of PCB Hot Spot Effect in Walleye Sander vitreus from Lower Green Bay of Lake Michigan - Charles P. Madenjian; Daniel J. Dembkowski; Daniel A. Isermann; Stuart A. Batterman; Sergei M. Chernyak; Stewart F. Cogswell; Mark E. Holey (Archives of Environmental Contamination and Toxicology, 2019)

Air pollutant strategies to reduce adverse health impacts and health inequalities: a quantitative assessment for Detroit, Michigan - Sheena E. Martenies; Chad W. Milando; Stuart A. Batterman (Air Quality, Atmosphere & Health, 2018)

Composition and Integrity of PAHs, Nitro-PAHs, Hopanes, and Steranes in Diesel Exhaust Particulate Matter - Lei Huang; Stanislav V. Bohac; Sergei M. Chernyak; Stuart A. Batterman (Water, Air, & Soil Pollution, 2013)

Evaluating the environmental performance of passenger vehicles - Stuart A. Batterman; William O. Mattick; Lawrence I. Ranka (The International Journal of Life Cycle Assessment, 2001)

Breath, urine, and blood measurements as biological exposure indices of short-term inhalation exposure to methanol - Stuart A. Batterman; Alfred Franzblau; James B. D'Arcy; Nicholas E. Sargent; Kenneth B. Gross; Richard M. Schreck (International Archives of Occupational and Environmental Health, 1998)

Environmental Reporting by the Fortune 50 Firms - Paige Davis-Walling; Stuart A. Batterman (Environmental Management, 1997)